Istikhdām Wa-Faʿāliyyah Wa-Muʿawwiqāt Adawāt At-Talʿīb Ar-Raqamī: Kāhūt Wa-Kuwīzz Fī Taʿlīm Al-Lughah Al-ʿarabiyyah – Murājaʿah Manhajiyyah - Abdullah Syihabuddin; Nelly Husni Laely; Durtam Sayidi (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2026)
Digital quiz-based learning platforms such as Kahoot and Quizizz are increasingly popular in Arabic language instruction. This study aims to describe the use of Kahoot and Quizizz in Arabic language learning, analyze their impact on learning outcomes, and identify the obstacles teachers face. The study uses a qualitative approach and a Systematic Literature Review, following the PRISMA guidelines. Articles were obtained through searches of the Google Scholar and Crossref databases, covering the period 2020 to 2025, then selected using inclusion criteria and quality assessment, resulting in 10 relevant articles. The synthesis results show that Kahoot and Quizizz are used as interactive quiz media to reinforce mufrodat, qawaid, maharah istima, and writing skills, making learning more varied and interesting. Most studies reported increases in average scores, learning completeness, motivation, and student engagement after integrating these two media. However, implementation is still hampered by teachers' digital competence, limited infrastructure, and a lack of time and training. This study emphasizes the need for institutional support to ensure the optimal use of digital gamification media in Arabic language learning.